Interplay among differential exposure to Mycobacterium leprae and TLR4 polymorphism impacts the immune response in household contacts of leprosy patients - Cunha, Eloisa Helena Medeiros; Marçal, Pedro Henrique Ferreira; Gama, Rafael Silva; de Oliveira, Lorena Bruna Pereira; Pinheiro, Roberta Olmo; Sarno, Euzenir Nunes; Brito-de-Sousa, Joaquim Pedro; de Souza, Márcio Luís Moreira; Fairley, Jessica Kathleen; Valente, Thaisa Netto Souza; Velloso-Rodrigues, Cibele; Martins-Filho, Olindo Assis; et al. (Frontiers in Immunology, 2023)
The aim of the present study was to investigate the association between the single nucleotide polymorphism (SNP) rs1927914 A/G in TLR4 gene and the immunological profile of household contacts (HHC) of leprosy patients. Leprosy classification is usually complex and requires the assessment of several clinical and laboratorial features. Herein, we have applied distinct models of descriptive analysis to explore qualitative/quantitative changes in chemokine and cytokine production in HHC further categorized according to operational classification [HHC(PB) and HHC(MB)] and according to TLR4SNP. Our results showed that M. leprae stimuli induced an outstanding production of chemokines (CXCL8;CCL2; CXCL9; CXCL10) by HHC(PB), while increase levels of pro-inflammatory cytokines (IL-6; TNF; IFN-; IL-17) were observed for HHC(MB). Moreover, the analysis of chemokine and cytokine signatures demonstrated that A allele was associated with a prominent soluble mediator secretion (CXCL8; CXCL9; IL-6; TNF; IFN-). Data analysis according to TLR4 SNP genotypes further demonstrated that AA and AG were associated with a more prominent secretion of soluble mediators as compared to GG, supporting the clustering of AA and AG genotypes into dominant genetic model. CXCL8, IL-6, TNF and IL-17 displayed distinct profiles in HHC(PB) vs HHC(MB) or AA+AG vs GG genotype. In general, chemokine/cytokine networks analysis showed an overall profile of AA+GA-selective (CXCL9–CXCL10) and GG-selective (CXCL10–IL-6) axis regardless of the operational classification. However, mirrored inverted CCL2–IL-10 axis and a (IFN-–IL-2)-selective axis were identified in HHC(MB). CXCL8 presented outstanding performance to classify AA+AG from GG genotypes and HHC(PB) from HHC(MB). TNF and IL-17 presented elevated accuracy to classify AA+AG from GG genotypes and HHC(PB) (low levels) from HHC(MB) (high levels), respectively. Our results highlighted that both factors: i) differential exposure to M. leprae and ii) TLR4 rs1927914 genetic background impact the immune response of HHC. Our main results reinforce the relevance of integrated studies of immunological and genetic biomarkers that may have implications to improve the classification and monitoring of HHC in future studies.